The comperative perceived desirability and feasibility of enterpreneurship within Greek schools - Drakopoulou Dodd, Sarah; Komselis, Alexis; Hassid, Joseph (SPOUDAI Journal of Economics and Business, 2009)
It is generally assumed that extensive provision of enterprise education will result in high levels of entrepreneurship. Greek data appears to run counter to this assumption. Greece consistently shows high levels of business start-up, and intention to act entrepreneurially. Yet there is very little provision of enterprise education within Greek schools. The aim of this paper is to draw on comparative data from across European schools to explore this Greek counterexample, by identifying and analyzing a range of enterprise cognitions. Specific attention is paid to enterprise intention, to the perception that entrepreneurship is a desirable or feasible career option, and to previous exposure to entrepreneurial experiences. The field data was gathered from more than 500 schools stake holders in seven European countries. Our main findings are that in Greece there is a higher than average intention to start a business even during childhood. We also find that Greek students claim to know enough to start a business, although though they are the least likely European students to have been taught to do so in school. Moreover, Greece has the highest percentage of indirect enterprise experience via the parents. Finally, a significant finding is that despite high levels of intention, experience and perceived knowledge, Greek students appear to be afraid of anxiety and tenseness during start-up. Also, surprisingly, the entrepreneur has an overall negative connotation among them. JEL Classifications: L26, I28.